32. CONGENITAL CYST ADENOMATOID MALFORMATION: A LITERATURE REVIEW AND CASE REPORT (Vietnam Journal of Community Medicine, 2024)
Congenital Cyst Adenomatoid Malformation (CCAM), also known as Congenital Pulmonary Airway Malformation (CPAM), is an abnormality of lung tissue, containing many small cysts concentrated in clusters in the lung lobes, originating mainly from the bronchioles. About 70% are detected within the first week of life, 10% are diagnosed after 1 year, and reported cases in adults are very rare. CCAM can develop in any lobe of the lung, but most occur in the lower lobe. CCAM are connected to the bronchial tree and are supplied by the pulmonary artery; the absence of a feeding artery is rarely seen. Typical CCAM is divided into 3 main types (I – III) based on differences in histology, pathological manifestations, radiological manifestations and prognosis. Two additional types of CCAM have also been proposed, that are 0 type and IV type, based on the medical history found and the type of epithelial cells seen in the airways present in the abnormality. The term CPAM is proposed to include these types of extensions. We report 1 cases of CCAM, diagnosed by postoperative pathology. We will also update related documents about this abnormality in the article with the hope of providing colleagues with an overview and approaches to diagnosis and treatment when encountering similar cases.
Keywords: Congenital adenoid cystic abnormalities, pulmonary adenoid cysts, pulmonary cystic abnormalities, multiple pulmonary cysts.